The Development of Problem Based Learning (PBL) Module on Mathematical Logic Course - Riska Novia Sari; Yessy Yusnita (UIR PRESS, 2018)
This study aimed at developing and to determining a qualified teaching materials in the form of Problem Based Learning (PBL) module on Mathematical Logic Course. PBL module is a form of systematic teaching material to support the learning process that can also be studied by students independently with authentic and meaningful problems or situations. This research can be catagorized as Research and Development or R&D. This development model was employing 4-D model with 4 stages of define, design, develop and disseminate stages. In this study, there was only 3 stages that were performed, namely define, design, and develop. The research instrument was using a module validation sheet. The product assessment was carried out by three validators consisting of two material experts and a media expert who were the lecturers of mathematics education study program. The results showed that the assessment of the two material validators towards PBL module on Mathematical Logic Course indicating the total mean score of 3.65 with the “very valid” criteria while, according to the media experts, the total mean score was 3.8 that can be catagorized as “very valid”. It means that the developed PBL module on Mathematical Logic Course has fulfilled the valid criteria, so it is feasible to be used in mathematics logic lectures. Keywords: Module, Mathematical Logic, Problem Based Learning